Pengaruh Pelayanan Sarana dan Prasarana Dalam Meningkatkan Mutu Pendidikan Di Sekolah UPT SD Negeri 060806 - Rizki Akmalia; Hasriyati Harahap; Tarisa Munawwarah; Zulqaidah Zulqaidah; Ade Irvan Margolang (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2024)
The purpose of this research is to explain the facilities and infrastructure services to improve the quality of education, the facilities and infrastructure that have been provided for students, the efforts made by the school so that students are interested in using the facilities and infrastructure provided, and the efforts made by the school principal to continue providing facilities and infrastructure in schools. This research method uses a qualitative research approach through research processes such as observation, interviews, literature and documentation. The results of the research show that the UPT SD Negeri 060806 school has implemented the required facilities and infrastructure provided by the school itself and was well received by all students and educators at the school so that the learning process carried out can be helped by the existence of this special service. creating a productive learning atmosphere to produce outstanding students to continue to improve the quality of national education.